(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
In the article, the content of the activities related to the selection and placement of candidates for the service of the internal affairs bodies and ensuring the stability of personnel, as well as the issue of selecting candidates for the service of the internal affairs bodies, the opinions on whether to search for personnel from among the candidates who have been positively described in the armed forces and have served and released to the reserve of the armed forces given Problems related to the process ofselecting personnel for the service of internal affairs bodies, relevant regulatory and legal documents were analyzed, proposals and recommendationsfor improving the field were developed.